Development of Learning Media for Running Game Variations Packaged in Articulate Storyline - Ari Wibowo Kurniawan; Ristyo Novy Wulandari (UNIVERSITAS NEGERI MAKASSAR, 2022)
Learning conditions in elementary schools at the time of the Covid-19 virus pandemic resulted in students studying at home with an online system, for PJOK subjects, interesting and precise learning media were needed, and the variety of existing games would make students enthusiastic about learning PJOK. The purpose of this research is to develop a learning media product of variations of locomotor running motion games packaged in the Articulate Storyline for the fourth-grade elementary school KKG PJOK in Sukun District, Malang City. The development method used is the Research and Development (R&D) approach with a development research model. The results of the evaluation of learning experts were obtained at 73%, the results of the evaluation of media experts were obtained at 96%, the results of the expert game analysis were obtained at 95%, and the results of the analysis of PJOK experts were obtained 75%, the results of the analysis of athletic experts were obtained large group trials obtained 90%. Based on these results, it is concluded that the products produced are stated to have accuracy, attractiveness, suitability, ease, clarity, and effectiveness for use.